2017
DOI: 10.25103/jestr.101.07
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Sulphate Attacks on Mortars - Influence of Temperature, Type of Sand and Type of Cement

Abstract: In this paper, an experimental study describing the coupling between temperature and external sulphate attacks on cementitious materials is performed. Cubic mortar specimens made of three types of cement, and two types of sand, i.e. silica sand and limestone sand. The mortars prepared, were then immersed in a 5% MgSO4 solution, at 5, 20 and 50 °C, for 12 months. No damage was observed on the samples exposed to the sulphate solution at 20, and 50 °C. However, serious damage was noted on mortars made with silica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…If Mg 2? ions are also present, the leaching of C-S-H phases occur, and thus the mortar loses structural integrity [115].…”
Section: Weak Trass-lime Repointing Mortarsmentioning
confidence: 99%
“…If Mg 2? ions are also present, the leaching of C-S-H phases occur, and thus the mortar loses structural integrity [115].…”
Section: Weak Trass-lime Repointing Mortarsmentioning
confidence: 99%
“…On the other hand, the leaching of the calcium from the C-S-H phases leads to the loss of the mechanical resistance of the paste. The literature has shown that the presence of Mg 2+ ions (in case of attack by magnesium sulfate) cause decalcification of C-S-H (by ion substitution), increasing the degree of alteration [72].…”
Section: Water Vapor Permeability and Water Absorptionmentioning
confidence: 99%
“…The presence of non-carbonated portlandite prevents the formation of expansive sulfates, possibly due to the precipitation of magnesium hydroxide (brucite) and avoiding the Ca-leaching of the C-S-H gel. As a consequence, the lasting of the samples increased [71][72][73]. Freeze-thaw cycles…”
Section: Water Vapor Permeability and Water Absorptionmentioning
confidence: 99%
“…Chlorides are known to be accelerators of compressive strength development in mortars or concrete [1]. On the other hand, WLI was found to have a higher sulphate concentration than SW. Mortar prisms subjected to it were expected to suffer more from sulphate attack [36][37][38]; this was observed in this study.…”
Section: Chemical Analysis Of Sw and Wlimentioning
confidence: 65%